2014
DOI: 10.14507/epaa.v22.1599
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Admission Criteria for Early and Mid-Career Students: Evidence from a U.S. MPA Program

Abstract: As applications for graduate and professional degree programs have reached unprecedented levels over the past decade, the applicant pool has become more diverse with more mid-career students deciding to return to school. Given the growth and diversification of the graduate applicant pool, many graduate programs are struggling to develop stronger admission package criteria that assure students admitted to their program have the pre-requisite skills needed to succeed. We examine which commonly used graduate admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…These results were consistent with the earlier findings of MPA students by Leavitt, Lombard and Morris (2011), although the latter results did not find the GRE scores to be significantly related to program GPA. The results of Darolia et al (2014) were also consistent with those of Ragothaman, Carpenter, and Davies (2009), although these authors also found significant correlations between graduate GPA and scores on the quantitative portion of the Graduate Management Admission Test (GMAT). Graham (1991) conducted a retrospective study of recent graduates of a Master of Business Administration (MBA) program.…”
Section: Reviewsupporting
confidence: 84%
See 1 more Smart Citation
“…These results were consistent with the earlier findings of MPA students by Leavitt, Lombard and Morris (2011), although the latter results did not find the GRE scores to be significantly related to program GPA. The results of Darolia et al (2014) were also consistent with those of Ragothaman, Carpenter, and Davies (2009), although these authors also found significant correlations between graduate GPA and scores on the quantitative portion of the Graduate Management Admission Test (GMAT). Graham (1991) conducted a retrospective study of recent graduates of a Master of Business Administration (MBA) program.…”
Section: Reviewsupporting
confidence: 84%
“…The following review provides evidence from five fields of study outside of communication sciences and disorders (CSD), followed by a review of two studies in CSD (see Table 1). Darolia, Ptochnick, and Menifield, (2014) examined the records of 223 Master of Public Affairs (MPA) applicants. The authors noted that grade point average (GPA) could be an unreliable variable in predicting graduate school success due to grade inflation, with a concern regarding its use as an exclusive criterion for admission.…”
Section: Reviewmentioning
confidence: 99%
“…Previous studies validated this non-significant finding, determining that age was not a statistically significant variable between doctoral completers and non-completers (Dunnerstick, 1990;Quinn, 1991;Valentine, 1986Valentine, , 1987). Yet increasingly applicants to graduate programs are on average older and more diverse; this change in the applicant pool requires programs to examine their admission criteria to reflect the evaluation of a changing applicant population (Darolia et al, 2014). In this study, the average age of the graduated group at time of admission was almost 28 years of age; this varies from the student that completes undergraduate studies and moves immediately into graduate school.…”
Section: Agementioning
confidence: 95%
“…It is also considered to be an accurate representation of a student's performance and potential. This is supported by a number of studies that identify a strong link between first-year GPA and end of studies performance [4,5] or end of studies GPA with professional success [6] or success in graduate studies [7][8][9][10][11], although studies also exist that question the strength of such links [12][13][14].…”
Section: Introductionmentioning
confidence: 92%